THE IMPLEMENTATION OF GOOGLE SPREADSHEETS AS A MEANS OF MONITORING STUDENT PROGRESS VALUE IN THE ECONOMIC EDUCATION PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, LAMBUNG MANGKURAT UNIVERSITY - Amima, Sharfina Puteri; Iskandar, Rizal; Rahmattullah, Muhammad; Ratumbuysang, Monry Fraick Nicky Gillian; Iffansyah, Muhammad (International Conference On Social Science Education, 2024)
By collecting and analyzing data on student learning outcomes, monitoring tools provide a comprehensive picture of student learning, thereby enabling an objective evaluation. The information held by monitoring is a summary of information from a tool. In the current digital era, the SIMARI system at Lambung Mangkurat University is not yet equipped with a monitoring feature that allows real-time monitoring of student study results. Implementing Google Spreadsheets as a monitoring tool can be an effective solution for comprehensively managing and analyzing student assessment data. This system identification process includes data collection stages through observation and interviews, needs analysis, and final implementation using Google Spreadsheets. Natively, Google Sheets enables faster and more informed decision-making regarding student assessments through real-time data access and extensive visualization.